UPAYA MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI MELALUI BERMAIN LOGICO - Rusmiati Rusmiati; Indrawati Noor Kamila (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2018)
Early childhood is a child in the age range of 0-6 years who are experiencing growth and development so that the right stimulation is needed in order to grow and develop optimally. Cognitive development in early childhood is very important so that children are able to explore the world around them. Through cognitive development, the function of thinking can be used quickly and precisely in overcoming a problem in overcoming a problem. Through learning games will be honed fun and can be absorbed by children to the maximum. The purpose of this study was to determine the learning process with logico playing media in an effort to improve cognitive development in early childhood group B TPA Al-Falah, Cijeungjing District, Ciamis District through the Logico game. A game that uses a Logico board with questions sheets. The research method used was classroom action research using a research model by Jhon Elliot. The research subjects were group B students (ages 4-5 years). The academic year 2019/2020 TPA Al-Falah, Cijeungjing District, Ciamis Regency, amounted to 10 children. In this class action research, the object of research is an effort to improve cognitive development of early childhood through the game of Logico in group B. Children data collection methods used are observation, interviews and documentation. The instruments used were development assessment instruments, research instruments, observations. This Classroom Action Research was conducted in three cycles and each cycle had one meeting. The results prove that playing Logico can improve cognitive development of early childhood, as evidenced by seeing the results of calculations in each aspect of observation has increased in each cycle. For the results of cognitive development in the pre-cycle play stage showed 32.5% while the first cycle increased 42% in the second cycle increased again to 55% while in the third cycle increased to 75%. In the Logico game to improve cognitive development of early childhood, a teacher is recommended to prepare things that support the implementation of the game such as an interesting game in accordance with the needs of children.